PESAN PENDIDIKAN DALAM REPRESENTASI GRAF KORELASI NOMOR JUZ DAN JUMLAH SURAH ALQURAN - Yuda Satria Nugraha (Koordinat Jurnal MIPA, 2020)
Graph representation is a very interesting study and it is important to look for a meaningful discussion in various fields. This paper is agreed upon in reviewing the educational message in the graph representation of the sign of juz number and number of the surah of the Koran. In determining these considerations, the results obtained are made of 5 types of graphs, namely P2, P3, S4, S7, and S13. These results are supported by the revised coefficient r statistical value. Correlations wrote in the Koran for example in the QS. Yusuf/12: 111, Q.S. Saba/34: 6, and Q.S. Shad/38: 29. One of the messages of education needed in this study is that it discusses education as a completely structured process, by making faith a foundation for every science that makes up godliness in thinking, speaking, and discussing in private as well as socially.